Islamic Influence on Malaysian and Turkish Society: The Spirit of Tolerance - Zainab Meher Khan; Humaira Jahangir (International Research Journal of Arabic and Islamic Studies, 2024)
Over the course of its more than 1,000-year history, Islam has been a major force in fostering peace and tolerance among other cultures. Islamic teachings have always placed a strong emphasis on peaceful coexistence and interfaith discussion, which are rooted in the Qur'anic values of justice, compassion, and respect for variety. This essay examines Islam’s role in promoting cultural diversity and societal cohesiveness from a historical, theological, and modern standpoint. understanding, rahma (mercy), and adl (justice), which offer a moral foundation for peaceful intergroup interactions. The study also looks at historical instances where Muslim cultures protected and accommodated a variety of religious and ethnic groups, such as the Ottoman Empire’s pluralistic policies and the convivencia in Andalusia. Through programs in education, diplomacy, and community involvement, Islamic scholars and institutions still promote tolerance and peaceful coexistence in contemporary settings. The study emphasizes how Islamic beliefs can be effective weapons against sectarianism, and cultural polarization when understood in their contextual and comprehensive aspects. Islam helps to create inclusive societies that respect the rights and dignity of every person, regardless of background, by encouraging respect for one another and a common set of human values. The article ends by urging fresh academic and interfaith initiatives to highlight Islam’s long history of tolerance and to combat falsehoods that sow discord. In a globalized world where multicultural contact and obstacles are growing, it is crucial to comprehend Islam's true position on harmony and coexistence.